Radial Extracorporeal Shock Wave Therapy Enhances the Proliferation and Differentiation of Neural Stem Cells by Notch, PI3K/AKT, and Wnt/β-catenin Signaling. Issue 1 (December 2017) - Zhang, Jing; Kang, Nan; Yu, Xiaotong; Ma, Yuewen; Pang, Xining
Abstract Neural stem cell (NSC) proliferation and differentiation play a pivotal role in the repair of brain function in central nervous system (CNS) diseases. Radial extracorporeal shock wave therapy (rESWT) is a non-invasive and innovative treatment for many conditions, yet little is known about the effects of this treatment on NSCs. Mouse NSCs (NE-4C) were exposed to rESWT with 1.0, 1.5, 2.0, 2.5, 3.0, and 3.5 bar (500 impulses, and 2 Hz)in vitro . Cell viability test results indicated that rESWT, at a dose of 2.5 bar, 500 impulses, and 2 Hz, increased NE-4C viability within 72 h, and that the PI3K/AKT pathway was involved in its mechanisms. Exposure to rESWT also affected proliferation and differentiation of NE-4C after 8 weeks, which may be associated with Wnt/β-catenin and Notch pathways. This assessment is corroborated by the ability of inhibitors of Wnt/β-catenin [Dickkopf-1 (Dkk-1)] and the Notch pathway (DAPT) to weaken proliferation and differentiation of NSCs. In summary, a proper dose of rESWT enhanced NSCs augment via the PI3K/AKT pathway initially. Also, Wnt/β-catenin and the Notch pathway play important roles in regulation of the long-term efficacy of rESWT. This study reveals a novel approach to culture NSCsin vitro and support neurogenesis.